Autologous adipose-derived stem cells: Basic science, technique, and rationale for application in ulcer and wound healing. (April 2017) - Zollino, Ilaria; Zuolo, Michele; Gianesini, Sergio; Pedriali, Massimo; Sibilla, Maria Grazia; Tessari, Mirko; Carinci, Francesco; Occhionorelli, Savino; Zamboni, Paolo
Objectives: The present review represents a translational boundary between basic research and surgery, particularly focusing on the promising application of adipose-derived stem cells harvested intra-operatively during debridement of venous leg ulcers. Methods: We reviewed 830 out of 5578 articles on MEDLINE starting from 1997 and sorted by the relevance option. Results: The technique currently used for adipose-derived stem cells intra-operative harvesting is presented, including a safety evaluation on a cohort of 5089 revised patients who underwent plastic surgery and maxillo-facial surgical procedures. Complications were reported in 169 cases (3.3%). One hundred and forty-one (2.77%) patients were classified as having minor complications, specifically: nodularity/induration 93 (1.83%), dysesthesia 14 (0.26%), hematoma 12 (0.23%), superficial infection 11 (0.21%), pain 7 (0.13%), poor cosmesis 3 (0.06%), and abnormal breast secretion 1 (0.02%), while 28 patients (0.55%) were classified as having major complications, specifically: deep infection 22 (0.43%), sepsis 3 (0.06%), abdominal hematoma 2 (0.04%), and pneumothorax 1 (0.02%). Application of cell therapy in venous leg ulcer is currently used only for patients not responding to the standard treatment. The review shows the lack of randomized clinical trials for application of adipose-derived stem cells among treatments for venous leg ulcer. Finally, adipose-derived stem cells implantation at the wound site promotes a new tissue formation rich in vascular structures and remodeling collagen. Conclusion: Adipose-derived stem cells strategy represents a great opportunity for the treatment of chronic wounds, due to the simplicity of the technique and the application of cell treatment in the operating room immediately following debridement. However, clinical studies and data from randomized trials are currently lacking.